Volition and its relation with the Positive Discipline for the pupils of primary schools (Journal of the College of Basic Education, 2022)
The objectives of the study as follows:Measuring of the Volition of the sixth class pupils in primary schools.The significance of the differences in the Volition of the sixth primary class students, according to the gender variable (male - female).Measuring the degree of the Positive Discipline of the sixth class pupils in primary schools.The significance of the differences in the Positive Discipline of the sixth primary class students, according to the gender variable (male - female).Identification of the relation between Volition and Positive Discipline. of the sixth class pupils in primary schoolsTo achieve the research objectives, the researcher prepared the will scale according to theory (Erikson 1982) and adopted the measure of positive discipline for the researcher (Moody 2015). The will scale consists of (22) items in its final form, while the positive discipline scale consists of (46) items in its final form. Both measures were applied to the research sample, which consists of (200) male and female students who were randomly selected from the research community, after data collection was statistically processed using educational and psychological sciences (spss) .The research concluded the following results: 1. The pupil of the sixth class enjoy a good level Volition2. There is no difference in the Volition according to the gender variable (male - female).The pupil of the sixth class enjoy a good level Positive Discipline4. There is no difference in the Positive Discipline according to the gender variable (male - female).5. There's a positive correlation relation between the Volition and Positive Discipline.The researcher submitted some recommendations and suggestions